Working capital and liquidity to the profitability of manufacturing companies listed on the IDX in 2019-2022 - Rahmawati, Mulia; Anggraeni, Putri Riana; Maulan, Shobha Tsaqofa; Haryadi, Didit (International Journal of Applied Finance and Business Studies, 2024)
This study investigates the interaction between modes of employment, profitability, and market liquidity in the manufacturing sector. The goal is to gain insight into how these factors interact and affect the overall value of a company in a particular region and industry. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of 10 manufacturing companies. This study examines the relationship between working model, profitability, and market liquidity through statistical analysis and regression modeling techniques. The results showed that working capital has no effect on profitability, liquidity significantly impacts profitability in the manufacturing industry, and operating capital and liquidity simultaneously affect profitability. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the manufacturing sector. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive corporate value in the industry, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management.